2021
DOI: 10.1038/s41598-021-96761-2
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic acid attenuates isoproterenol-induced cardiac hypertrophy via downregulation of ROCK1–Sp1–PKCγ axis

Abstract: Cardiac hypertrophy is an adaptive response of the myocardium to pressure overload or adrenergic agonists. Here, we investigated the protective effects and the regulatory mechanism of protocatechuic acid, a phenolic compound, using a mouse model of isoproterenol-induced cardiac hypertrophy. Our results demonstrated that protocatechuic acid treatment significantly downregulated the expression of cardiac hypertrophic markers (Nppa, Nppb, and Myh7), cardiomyocyte size, heart weight to body weight ratio, cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…20 The transcription factors GATA4, GATA6 and SP1 are reported to induce cardiac hypertrophy. 14,21 However, EREG does not directly increase cardiomyocyte size. The findings of this study suggest that EREG partially contributes to cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…20 The transcription factors GATA4, GATA6 and SP1 are reported to induce cardiac hypertrophy. 14,21 However, EREG does not directly increase cardiomyocyte size. The findings of this study suggest that EREG partially contributes to cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, EREG promoted the migration of salivary adenoid cystic carcinoma cells by upregulating the phosphorylation of ERK, Akt, STAT3 and EGFR 20 . The transcription factors GATA4, GATA6 and SP1 are reported to induce cardiac hypertrophy 14,21 . However, EREG does not directly increase cardiomyocyte size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, mutated PKCε gene regulated its own transcription. Studies also indicated that Ap1 regulates the expression of PKC iota in cardiac hypertrophy [ 81 ]. This might be the principal mechanism behind the PKCε pathogenicity in different diseases specifically cancers, where its over expression is frequently reported.…”
Section: Discussionmentioning
confidence: 99%